2020
DOI: 10.1155/2020/3695952
|View full text |Cite
|
Sign up to set email alerts
|

Goiter and Its Associated Factors among Adolescent High School Girls at Tach Armachiho District, Northwest Ethiopia: An Institution-Based Cross-Sectional Study

Abstract: Introduction. In Ethiopia, iodine deficiency disorder (IDD) is a major public health problem. The most visible effect of IDD is the appearance of goiters, and 28 million people are affected by goiter. Therefore, this study aimed to assess the prevalence and associated factors of goiter among high school adolescent girls at Tach Armachiho district, Northwest Ethiopia. Methods. An institution-based cross-sectional study was conducted from October to November 2018. A total of 620 high school adolescent girls were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…We failed to show an association between iodine status and thyroid goiter in the univariate logistic analysis, but we did find that residents living in rural areas were more likely to have goiter after adjusting for multiple associated factors. This result was in line with the findings of a previous study conducted in Ethiopia, which indicated that high school girls living in rural areas had an increased odds of thyroid goiter than those living in urban settings ( 25 ). The higher prevalence of thyroid goiter in rural residents may be related to a lack of education.…”
Section: Discussionsupporting
confidence: 92%
“…We failed to show an association between iodine status and thyroid goiter in the univariate logistic analysis, but we did find that residents living in rural areas were more likely to have goiter after adjusting for multiple associated factors. This result was in line with the findings of a previous study conducted in Ethiopia, which indicated that high school girls living in rural areas had an increased odds of thyroid goiter than those living in urban settings ( 25 ). The higher prevalence of thyroid goiter in rural residents may be related to a lack of education.…”
Section: Discussionsupporting
confidence: 92%
“…ere is an inconsistency of findings in Ethiopia, and no studies have been done using the titration method in the current study area. Furthermore, the study area has a high prevalence of goiter, implying that iodized salt utilization will be poor [35,36]. erefore, this study used gold standard IDTM to assess the prevalence of adequately iodized salt usage and associated factors at the HH level in Tachar Amchio district, Northwest Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, the overall pooled prevalence of adequate iodine level of iodized dietary salt in households in Ethiopia was 44.37% (95% CI: 35.85–52.88) and the prevalence ranges from 17.5 ( 19 ) to 73% ( 20 ) ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 86%